USING GOOGLE CLASSROOM TO TEACH READING HORTATORY EXPOSITION TEXT - Irwan Sulistyanto; Dina Azmi Imada (Universitas Muhammadiyah Mataram, 2020)
Abstract: Google Classroom is an appropriate Learning Management System (LMS) in teaching reading. Google Classroom helps students get easier in comprehending the text. This research intended to know the effectiveness of using Google Classroom to teach reading hortatory exposition text. Quantitative was chosen as the research approach, while the research design used was posttest-only control group design. This research used two classes that become an experimental class and control class. The experimental class was taught reading using Google Classroom, while the control class was taught with conventional teaching. To collect the data, post-reading comprehension tests in experimental and control classes were administered. Data were analyzed using mean scores, standard deviation, and independent-sample t-test. The findings showed that sig. the score was lower than the level of a significant 5%. It can be concluded that using Google Classroom to teach reading hortatory exposition text is effective.Abstrak: Google Classroom adalah Learning Management System (LMS) yang sesuai dalam mengajar membaca. Google Classroom membantu siswa siswi dalam memahami bacaan dengan mudah. Penelitian ini bertujuan untuk mengetahui efektifitas penggunakan Google Classroom untuk mengajar membaca text hortatory exposition. Kuantitatif dipilih sebagai pendekatan penelitian sedangkan design penelitian yang digunakan adalah posttest-only control group. Penelitian ini menggunakan dua kelas yaitu kelas eksperimen dan kelas control. Kelas ekperimen diajar membaca dengan menggunakan Google Classroom sedangkan kelas control diajar menggunakan conventional teaching. Untuk mengumpulkan data, tes akhir pemahaman membaca di kelas ekperimen dan control digunakan. Data yang terkumpul dianalisis menggunakan nilai rata-rata, standar deviasi dan independent sample t-test. Dari hasil yang diperoleh menunjukkan bahwa nilai signifikansi lebih rendah dari pada taraf signifikansi 5%. Ini dapat disimpulkan bahwa menggunakan Google Classroom untuk mengajar membaca teks hortatory exposition adalah efektif.